A Possible Association Between Dry Eye Symptoms and Body Fat: A Prospective, Cross-Sectional Preliminary Study. Issue 4 (July 2017) - Ho, Kam Chun; Jalbert, Isabelle; Watt, Kathleen; Golebiowski, Blanka
Abstract : Objectives: To examine the relationship between dry eye symptoms and adiposity in a population study. Methods: A prospective cross-sectional single-visit preliminary study was designed to sample ocular symptoms and indices of adiposity in the general adult population. Patients recruited from the UNSW optometry clinic, the university campus and surrounding community, and overseas were invited to complete a survey composed of the short form Dry Eye Questionnaire (SFDEQ) (Dry Eye Questionnaire-5 or Contact Lens Dry Eye Questionnaire-8) and the Ocular Comfort Index (OCI) via hardcopy or online. Participants self-measured their weight, height, waist circumference (WC), and body fat % (optional). Associations between measures of adiposity (Body mass index [BMI], WC, and body fat %) and ocular symptoms scores (SFDEQ and OCI) were determined using Spearman correlation coefficients. Group differences were compared using independent t test. Results: Three hundred and five participants including 52 contact lens wearers completed the study and 78 of them measured body fat %. There was a moderate correlation between body fat % and dry eye symptoms (SFDEQ r =0.34, P =0.003; OCI r =0.32, P =0.004). The interaction between body fat % and gender, wear of contact lenses, and older age were shown to be significant predictors of less ocular comfort in multivariate analysis (F(3, 74) =12.13, P <0.001). Conclusions: An association between adiposity measured by body fat % and symptoms of dry eye was demonstrated in the general adult population. Confirmation of these findings in a large study is required. Abstract : Supplemental Digital Content is Available in the Text.